Changing requirements and resulting needs for IT-infrastructure for longitudinal research in the neurosciences. (January 2016) - Buckow, Karoline; Quade, Matthias; Rienhoff, Otto; Nussbeck, Sara Y.
Highlights: Requirements for an IT-infrastructure in neurosciences are getting more complex. Arising requirements as well as IT-solutions were identified and analyzed. The role of metadata in annotating research data is becoming more important. Professional IT-infrastructure involving ID-management and expert stuff is required. Abstract: The observation of growing "difficulties" in IT-infrastructures in neuroscience research during the last years led to a search for reasons and an analysis on how this phenomenon is reflected in the scientific literature. With a retrospective analysis of nine examples of multicenter research projects in the neurosciences and a literature review the observation was systematically analyzed. Results show that the rise in complexity mainly stems from two reasons: (1) more and more need for information on quality and context of research data (metadata) and (2) long-term requirements to handle the consent and identity/pseudonyms of study participants and biomaterials in relation to legal requirements. The combination of these two aspects together with very long study times and data evaluation periods are components of the subjectively perceived "difficulties". A direct consequence of this result is that big multicenter trials are becoming part of integrated research data environments and are not standing alone for themselves anymore. This drives up the resource needs regarding the IT-infrastructure in neuroscience research. In contrast to these findings, literature on this development is scarce and the problem probably underestimated.